Book review: Discerning critical hope in educational practices. Bozalek, V., Leibowitz, B., Carolissen, R. & Boler, M. (eds). - Behari-Leak, Kasturi (Critical Studies in Teaching and Learning, 2023)
Review of: Bozalek, V., Leibowitz, B., Carolissen, R. & Boler, M. (eds). 2014. Discerning critical hope in educational practices. Abingdon: Routledge.